2015
DOI: 10.1002/jcph.646
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic‐Pharmacodynamic Modeling of Intravenous and Oral Topiramate and Its Effect on the Symbol‐Digit Modalities Test in Adult Healthy Volunteers

Abstract: A sequential pharmacokinetic-pharmacodynamic (PK-PD) modeling approach was used to quantify the effects of a single dose of topiramate (100 or 200 mg) on working memory, attention, and psychomotor speed as measured by the Symbol-Digit Modalities Test (SDMT). Established on data pooled from 3 randomized, crossover studies in healthy subjects (19–55 years of age), using both oral and a novel stable-labeled intravenous (IV) formulation of topiramate, an inhibitory Emax model was found to characterize the topirama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Most studies were conducted in epilepsy patients in various age groups including infants, 24 infants and children, 19 children and adults, 25,26 and children, adults and elderly 21 . Moreover, three were conducted solely in adults with epilepsy, 18,20,22 and two studies in healthy volunteers 23,27 . The number of subjects and the number of observations varied across studies, ranging from 22 to 1217 and 118 to 4640, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most studies were conducted in epilepsy patients in various age groups including infants, 24 infants and children, 19 children and adults, 25,26 and children, adults and elderly 21 . Moreover, three were conducted solely in adults with epilepsy, 18,20,22 and two studies in healthy volunteers 23,27 . The number of subjects and the number of observations varied across studies, ranging from 22 to 1217 and 118 to 4640, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…All studies used NONMEM software for model development, with various estimation methods (Table 3). For the structural model development, six studies used a linear one‐compartment structure, 18,19,22,24–26 while three studies reported a two‐compartment linear model 20,21,27 and the other one used an E max model to describe the effects of single‐dose TPM on working memory, attention and psychomotor speed 23 . This model is commonly used to explain the concentration–effect relationship, in which E max is the maximal effect when all the receptors are occupied by the drug.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…vs IR topiramate b.i.d., but plasma concentration fluctuations may impact signature adverse cognitive effects such as word‐finding difficulty and psychomotor slowing. The occurrence and severity of these and other CNS AEs associated with topiramate are influenced by dose, rate of dose escalation, and plasma topiramate concentrations . Given this PK‐PD relationship, a bioequivalence study comparing an XR formulation (Trokendi XR q.d.)…”
Section: Extended‐release Topiramatementioning
confidence: 99%